Exact and approximate solutions to LQG homing problems in one and two dimensions. (19th December 2014) - Lefebvre, Mario; Zitouni, Foued
Summary: Stochastic optimal control problems in which two‐dimensional diffusion processes are controlled until they enter a given set are solved explicitly. When symmetry can be used, exact solutions are obtained. The same arguments are valid for one‐dimensional processes. In the general case, it is shown how to obtain good approximate solutions. Various examples are presented.